Use of nasal high flow oxygen during acute respiratory failure - Ricard, Jean-Damien (Intensive Care Med, 2020)
Nasal high flow (NHF) has gained popularity among intensivists to manage patients with acute respiratory failure. An important literature has accompanied this evolution. In this review, an international panel of experts assessed potential benefits of NHF in different areas of acute respiratory failure management. Analyses of the physiological effects of NHF indicate flow-dependent improvement in various respiratory function parameters. These beneficial effects allow some patients with severe acute hypoxemic respiratory failure to avoid intubation and improve their outcome. They require close monitoring to not delay intubation. Such a delay may worsen outcome. The ROX index may help clinicians decide when to intubate. In immunocompromised patients, NHF reduces the need for intubation but does not impact mortality. Beneficial physiological effects of NHF have also been reported in patients with chronic respiratory failure, suggesting a possible indication in acute hypercapnic respiratory failure. When intubation is required, NHF can be used to pre-oxygenate patients either alone or in combination with non-invasive ventilation (NIV). Similarly, NHF reduces reintubation alone in low-risk patients and in combination with NIV in high-risk patients. NHF may be used in the emergency department in patients who would not be offered intubation and can be better tolerated than NIV. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00134-020-06228-7) contains supplementary material, which is available to authorized users.